Legal Certainty in Filing for Interfaith Marriage Determination in General Courts - Hikmah, Nurul; Faisol, Syahid Akhmad; Hasyyati, Astrid Amidiaputri; Hermono, Budi; Puspytasari, Heppy Hyma (Laboratorium Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya (https://uinsa.ac.id/fsh/facility), 2025)
SEMA 2 of 2023, issued by the Supreme Court, is oriented towards standardizing court decisions related to registering interfaith marriages. On the other hand, SEMA 2 of 2023 has instead created problems, particularly concerning human rights. From the perspective of human rights, marriage is viewed as a personal right, and registration is one of the citizens' rights, meaning that the state must fulfill marriage. The author uses normative legal research, emphasizing legislative, conceptual, and comparative studies with other countries. The research results indicate that SEMA No. 2 of 2023 was issued to address legal uncertainty in the judiciary regarding diverse rulings on the validity of interfaith marriages by providing clear instructions to judges to reject requests for the registration of interfaith marriages. The legal implication of this SEMA is that interfaith marriages occurring after the issuance of SEMA cannot be registered with the Dispendukcapil without a court ruling as the basis for recognition, due to the non-retroactive nature of circular letters. SEMA No. 2 of 2023 not facilitating interfaith marriages legally in Indonesia as a concrete effort to clarify provisions that have not been regulated explicitly in the Marriage Law.